BIOSEDIMENTATION OF MANGANESE IN THE VICINITY OF DEEP-WATER HYDROTHERMAL VENTS, AS INDICATED BY SEDIMENTATION TRAP COLLECTIONS - Tambiyev S.B. (My University, 1989)
The bottom waters near hydrothermal vents of the Guaymas Basin show a great increase (by a factor of 20 to 130) in the biomass of benthopelagic zooplankton, with copepods predominant. It is most probable that it is these organisms that produced the manganese-rich fecal pellets. It appears that colonial bacterial aggregates, including aggregates of chemosynthetic bacteria, are one of the food sources of zooplankton in the open ocean and near the hydrothermal vents. These organisms, which occur in huge numbers in hydrothermal discharge areas, decompose hydrogen sulfide and other compounds issuing from the hydrotherms to derive material for the synthesis of their own biomass. In contrast to Fe, which occurs at equal concentrations in the capsules of living and dead bacteria, Mn is accumulated by living organisms. Furthermore, no other particles of suspended matter in the clouds with high manganese content showed significant (> 0.1 percent) concentrations of Mn; microanalysis of our samples of suspended matter and material from the sedimentation traps confirmed this result. A relationship between bacterial aggregates and Mn has also been directly indicated by the high concentrations of suspended matter in bottom waters of the Guaymas Basis, paralleling a rise in the concentrations of suspended Corg and Mn to Al in the suspended matter is higher in the clouds than in adjoining waters. Study results suggest a new mechanism of biogenic sedimentation of Mn in the discharge areas of deep-water hydrotherms, which the paper discusses.